(untitled) (International Educators Conference, 2025)
The article scientists who have studied the effect of stress on the structure and function of the liver have conducted a number of studies. Stress is a universal naspecific neurogormonal reaction of the body in the form of an injury that manifests itself with increased body resistance, or a voltage of non-specific adaptation mechanisms in response to a signal that threatens the life or well-being of the body.